On Frequency Scaling of Rain Attenuation - Fišer, Ondřej; Kovalchuk, Maria (IEEE (Institute of Electrical and Electronics Engineers), 2022)
In our paper we deal with the generalized method of frequency scaling. From the attenuation known at one frequency, we determine the rain rate by the inverse procedure of any rain attenuation prediction model, which we then use to estimate the rain attenuation on another frequency. We compare the results on one hand with exact values, on the other hand with the results after the ITU-R frequency scaling method. The method proposed by us seems to be more accurate at the level of instantaneous frequency scaling and also at the level of the attenuation distribution function.
O frekvenčním škálování útlumu deště
Keywords: Electromagnetic wave attenuation; Frequency bands; Inverse problems; Rain